THE EFFECTS OF TRAINING METHODS AND ACHIEVEMENT MOTIVATION TOWARD OF FOOTBALL PASSING SKILLS (Experiment Study Athlete at The Muspan FC Football School of Padang City, West Sumatera Provincial) - Syukur, Abdul; Soniawan, Vega (JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2015)
The purpose of this study was to determine the effect of the training methods of structured and play as well as achievement motivation on the passing skills of football. Research was conducted on athletes at the Muspan FC Football School of Padang. This type of research is experimental design was used treatment by the level of 2x2.The study population was all athletes the Muspan FC Football School of Padang, amounting to 134 athletes. Determination of the sample using purposive sampling technique is to set a mid- level athletes aged 13-15 years amounted to 74 athletes. Samples treated in this study were 40 athletes. The data obtained and analyzed by analysis of variance (ANAVA) and two lanes. and subsequently followed by Tuckeys test at a significance level Î± = 0, 05.The results showed that (1). Results of passing skills of football in the treatment of structured training method (A1) is higher than the results of play method (A2). (2). There is the influence of the interaction between training methods (A) and achievement motivation (B) the passing skills of football. (3). Results of passing skills of football on the treatment method structured exercise high achievement motivation (A1B1) higher than the results of the play method high achievement motivation (A2B1). (4). Results of passing skills of football in the treatment of structured training method low achievement motivation (A1B2) is lower than the play method low achievement motivation (A2B2).